Life Cycle Assessment of Reinforced Concrete Buildings in Seismic Regions - HALIM, ZABIHULLAH (İstanbul Kültür Üniversitesi, 2021)
The structural engineering profession has been developed significantly over the last decades as new systems, design methods, and other integrated approaches come to the field. From the 1950s and 60s onwards, cities throughout the world have expanded rapidly, high rise buildings increased, and cities expanded their occupied areas; in such circumstances, serious demand for sustainable development approaches can be observed, such as needs for setting some standards applicable in the local and global level. An integrated approach can help us properly address these debated issues. Experts from the sustainability field point out that materials and energy resources are limited, and the construction sector consumes a large portion of these remaining resources unquestionably. These points should be the main motivation for insisting on sustainable development approaches. However, it is a well-known fact that structural design engineers do not have a fundamental role in sustainable construction topics yet. Many approaches mainly focus on some specific topics of sustainability like environment and economy, whilst there is a need for an integrated approach to maintain a balance between all components of sustainability. There are many challenges that structural engineers face now a day, but the global environmental challenge is the most prominent of them. Within the scope of this thesis, it is aimed to determine and define how buildings in seismic regions affect sustainability by comparing steel and reinforced concrete frame structures. This comparison will be made using Athena Impact Estimator and SAP2000 by taking into account the environmental effects for the entire life cycle of reinforced concrete and steel frames in seismic regions.
▪ Yüksek lisans tezi.
Keywords: Reinforced Concrete; Buildings; Seismic Regions; Sustainability; Environmental Impacts; Greenhouse gases; Athena Impact Estimator